Dynamics of women’s Secure Land Rights for Sustainable Rural household Food Security in Uganda - Rwangire, Milton; Kabeba Muriisa, Roberts (Journal of African Interdisciplinary Studies (JAIS), 2021)
Food security is a major concern of a global agenda as reflected in the UN Post 2015 Sustainable Development Goals (United Nations, 2000, 2016). Globally more than 2 billion people are food insecure and this situation is on the rise and has turned into a crisis especially in Sub Saharan Africa. Uganda which was the focus of this paper has had multiple food crises in various regions at different times. Isingiro district where this chapter is situated has been experiencing food crisis in recent times. Women who are the main producers of food lack secure land rights to enhance food production. The goal of this study was to explore how women’s secure land rights can be strengthened to enhance sustainable rural household food security in Uganda. Our methodology was largely qualitative. We interviewed 102 respondents including local women, local leaders and key informants. We held three focus group discussions one in each sub-county where we collected data from. Our findings indicate that women have limited land rights with regard to control of land, but majority of them have access rights but with minimal decisions on what to produce. Our findings indicated that barriers to women to secure land rights are from institutional as well as lack of enforcement of the legal frameworks in place. Owing to the sensitivity of land ownership and patriarchal nature of Ugandan societies, Isingiro district in particular, we therefore concluded that secure land rights for women can be strengthened through active sensitization of both men and women on the value of women’s rights to land and its implication on sustainable rural household food security.
Keywords: Land Rights; Women; Rural Households; Food Security